2012
DOI: 10.7150/thno.3629
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotubes Interact with Macrophages and Influence Tumor Progression and Metastasis

Abstract: Macrophages are one of the most important types of immune effector cells and are closely associated with tumor progression and metastasis. In this work, we investigated the influences of oxidized multiwalled carbon nanotubes (o-MWCNT) on macrophages that are resting in the normal subcutis tissue or in the tumor microenvironment in vivo as well as on the macrophage cell line of RAW 264.7 treated with combination of IL4, IL10 and IL13 in vitro. The o-MWCNT were characterized with SEM, DLS, FTIR, TGA, and UV-vis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Our findings agree with previous studies showing that NM exposure changed macrophage and neutrophil concentrations and engulfed the exposed NM after intra-tracheal instillation in vivo [2729]. Macrophages invade lung interstices for cleaning function and take different phenotypes based on environmental signals, which might lead to pulmonary pathologies [30]. …”
Section: Discussionsupporting
confidence: 91%
“…Our findings agree with previous studies showing that NM exposure changed macrophage and neutrophil concentrations and engulfed the exposed NM after intra-tracheal instillation in vivo [2729]. Macrophages invade lung interstices for cleaning function and take different phenotypes based on environmental signals, which might lead to pulmonary pathologies [30]. …”
Section: Discussionsupporting
confidence: 91%
“…It is reported that long MWCNT (20 μ m) reduced the migratory capacity in primary human alveolar macrophages (AMs) along with increased expression of MARCO [ 23 ]. In contrast, MWCNT promoted cell migration in RAW263.7 macrophage cell lines and human microvascular endothelial cells (HMVEC) [ 24 , 25 ]. Our previous study also showed an increasing migration capacity of A549 cells after MWCNT exposure for 24 h at 30 μ g/mL [ 12 ], consistent with the finding in Pacurari et al's study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, although we studied the effects of MWNTs-associated photothermal therapy on tumor growth and cancer-induced bone destruction, we did not address the effects on other tumor-related factors, like macrophages. According to Yang et al , macrophages influenced by MWNTs plays an important role in the tumor progression and metastasis 31 . Thus, we should take macrophages into account in the further research.…”
Section: Discussionmentioning
confidence: 99%